Information and Communication Technologies of Ecuador (TIC.EC) - Botto-Tobar, Miguel; Barba-Maggi, Lida.; González-Huerta, Javier; Villacrés-Cevallos, Patricio; S. Gómez, Omar.; Uvidia-Fassler, María I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book constitutes the proceedings of the 6th Conference on Information Technologies and Communication of Ecuador "TIC-EC", held in Riobamba City from November 21 to 23, 2018, and organized by Universidad Nacional del Chimborazo (UNACH) and its Engineering School, and the Ecuadorian Corporation for the Development of Research and Academia (CEDIA). Considered as one of the most important ICT conferences in Ecuador, it brought together international scholars and practitioners to discuss the development, issues and projections of the use of information and communication technologies in multiple fields of application. Presenting high-quality, peer-reviewed papers, the book discusses the following topics: • Communication networks • Software engineering • Computer sciences • Architecture • Intelligent territory management • IT management • Web technologies • ICT in education • Engineering, industry, and construction withICT support • Entrepreneurship and innovation at the Academy: a business perspective The authors would like to express their sincere gratitude to the invited speakers for their inspirational talks, to the authors for submitting their work to this conference, and the reviewers for sharing their experience during the selection process.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence